Navigating Technostressors Mindfully: A Conceptual Understanding Using Psychological Needs Satisfaction - Ramesh, Rofia; V, Vijayalakshmi; Sharma, Piyush; Ananthram, Subra (2019)
Current approaches to reduce technostress are myopic as they underestimate the role of the individual’s agency in its amelioration and instead focus only on organisationprovided interventions. This conceptual paper uses the Job Demands-Resources (JD-R) theory in postulating mindfulness, an individual disposition amenable to development as a personal resource in alleviating techno-burnout and fostering work engagement among employees with intensive Information and communications technology (ICT) use. Further, we posit psychological need satisfaction as the psychological mechanism that contributes to differential perceptions of ICT use as stressful or not, thus differentiating them into challenge and hindrance demands. By introducing mindfulness as a personal resource, the research related contribution of this paper lies in two domains – as an individual mitigation approach within the technostress domain and as an emerging personal resource within JD-R theory in the organisational behaviour domain. Our propositions are proffered as a conceptual framework and we encourage future research to validate our contentions.